(untitled) (Research, Society and Development, 2020)
Introduction: The aging process is a global reality directly affecting the daily tasks and quality of life of the elderly. Due to the increase in population aging, the growth of chronic diseases is observed, with osteoarthrosis (OA) being the most prevalent. Aim: To evaluate the applicability of pain assessment instruments in elderly patients with knee osteoarthrosis. Methods: This is an observational, descriptive cross-sectional study with 22 participants with OA. An evaluation was performed using the socioclinical questionnaire, Visual Analog Scale, Brief Pain Inventory and the McGill Questionnaire. Finally, the data were submitted to statistical analysis considering the significance level of p <0.05. Results: It was found that the age group was 60-70 years, 95.2% was female, all participants had a diagnosis of OA. The instruments were applied in the following order: EVA, McGill and BPI. In Eva, the mean was 5.6 ± 2.74. In McGill, the mean score was 9.9 ± 14.7, and the numerical index of descriptors was 14.1 ± 6.0. In the BPI regarding the severity of pain, the mean score was 5.1 ± 2.1, as for the functional interference of pain, the score was 4.5 ± 2.5. Final Considerations: It was found in the present study that BPI was the instrument of greatest preference among participants (57.1%). It is observed the need to conduct further research involving the theme due to the scarcity of studies related to the theme.